Description of the Ability to Arrange Assessments According Curriculum 2013 on Chemistry PPG SM3T Student - Rahayu, Sri; Hairida, Hairida; Rasmawan, Rahmat; Sartika, Rody Putra; Hadi, Lukman (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The curriculum 2013 experienced a shift in the assessment process, which is from the assessment of results to the assessment process. In the process of carrying out the assessment, many complaints that arise in the field including the difficulty in determining the assessment of various aspects both cognitive, affective, and psychomotor. Researchers are interested in knowing how the ability of PPG SM3T Chemistry Education’s Students as a prospective professional teacher in compiling an assessment based on curriculum 2013. The research purposes were to describe the ability of PPG SM3T Chemistry Education’s Students in compiling an assessment based on curriculum 2013. The methode of the research was descriptive with study case involved 16 students of PPG SM3T Chemistry Education in the 2018/2019 school year. The research instrument was in the form of an assessment rubric with 10 aspects of assessment, one of which contained HOTS questions. The results of the data analysis showed that the ability of PPG SM3T Chemistry Education in compiling HOTS questions was classified as less skilled with an average score 67.19% whereas when viewed from all aspects of the preparation of the assessment based on curriculum 2013 it was classified as skilled with an average score 84.89%.